PENGARUH ENDORSEMENT DAN KREDIBILITAS INFLUENCER TERHADAP MINAT BELI PRODUK PARFUM MORRIS PADA TOKOPEDIA (Studi pada Gen Z di Kabupaten Tasikmalaya) - Faiz Basyar Sidiq; Herdiyanti Herdiyanti (Universitas Dharmawangsa, 2026)
Abstract: This study aims to analyze the effect of endorsement and influencer credibility on purchase intention for Morris Perfume products on Tokopedia, focusing on Generation Z in Tasikmalaya Regency. A quantitative method with a survey approach was employed, distributing questionnaires to 100 respondents selected through purposive sampling. Data were analyzed using multiple linear regression. The results indicate that: (1) Endorsement has a positive and significant effect on purchase intention (B = 0.384; t = 5.006; p < 0.05); (2) Influencer credibility has a positive and significant effect on purchase intention (B = 0.456; t = 5.959; p < 0.05). Simultaneously, both variables explain 91.1% of purchase intention variation (R² = 0.911; F = 496.632; p < 0.05). Influencer credibility proved to be the dominant factor with a higher beta coefficient (0.527) compared to endorsement (0.442), suggesting that Gen Z consumers prioritize the perceived trustworthiness, expertise, and attractiveness of influencers when deciding to purchase Morris Perfume on Tokopedia.